Design and validation of a questionnaire on the perception of cheating in traditional sporting games: CHEAT-1 - Sáez de Ocáriz, Unai; Lavega-Burgués, Pere; Pic, Miguel (Frontiers in Psychology, 2025)
IntroductionCheating in traditional sporting games (TSG) presents a significant challenge for values education and harmonious school coexistence. Despite its educational relevance, no validated instruments are currently available to assess students’ perceptions of cheating in TSG contexts.MethodsThis study aimed to design and validate the CHEAT-1 questionnaire, designed to assess perceptions of cheating in TSG. The instrument was created through a four-stage process involving item construction based on the internal and external logic of motor games, expert panel reviews (n = 13), and focus groups with students from primary, secondary, and university levels (n = 24). The preliminary version (46 items) was reduced to a final version of 18 items, structured in two dimensions: Internal Logic and External Logic. A sample of 564 students aged 10–30 completed the questionnaire.ResultsExploratory and confirmatory factor analyses supported a two-factor structure comprising Internal Logic and External Logic dimensions. The model demonstrated strong fit indices (RMSEA = 0.05; CFI = 0.98; TLI = 0.97). Internal consistency was high, with Cronbach’s alpha and McDonald’s omega coefficients both reaching 0.96. Content validity was confirmed, with all items exceeding a CVI of 0.80.DiscussionThe CHEAT-1 instrument demonstrates strong psychometric properties and fills a critical gap in the assessment of ethical behavior in Physical Education settings. Its application can support teachers in detecting students’ perceptions of cheating and implementing targeted pedagogical interventions. The tool offers a valuable resource for future research and practice in values-based education across different educational stages.